Ethics, Behaviors, and Characters of Memayu Hayuning Bawono, Ambrasto Dur Hangkoro Accountant in Java - I Made Laut Mertha Jaya; Tjiptohadi Sawarjuwono; Sungkono - Sungkono; Mar'a Elthaf Ilahiyah (Jurnal Kajian Akuntansi, 2021)
AbstractThe moral teachings and philosophy of life of the Javanese have a very deep meaning which leads to happiness. This paper aims to provide up-to-date knowledge about the meaning of Ethics, Behavior, and Character of Memayu Hayuning Bawono, Ambrasto dur Hangkoro in accounting profession education in Java, based on Javanese philosophy. This study uses a qualitative method approach, ethnography. The results of this study conclude that ethics, behavior, and character in accounting profession education based on Javanese philosophy are more bars, ruruh, wantah, duga prayoga, nastiti and do not focus on ardana. The character of "dhakah" in him slowly disappeared because the formed "warok" had reached "Wiloka". This finding provides a new aspect for the curriculum development of accounting education programs, so that graduates (accountants) can better understand and interpret the philosophy of human life from the point of view of Javanese philosophy.Keywords: Ethics; Behavior; Accountant profession education character.Abstrak Ajaran moral dan filosofi hidup orang Jawa memiliki makna yang sangat mendalam yang mengarah kepada kebahagiaan. Tulisan ini bertujuan untuk memberikan keterbaruan pengetahuan tentang makna Etika, Perilaku, dan Karakter Memayu Hayuning Bawono, Ambrasto dur Hangkoro pada pendidikan profesi akuntan di Jawa, berdasarkan filsafat Jawa. Penelitian ini menggunakan pendekatan metode kualitatif, etnografi. Hasil penelitian ini menyimpulkan bahwa etika, perilaku, dan karakter pada pendidikan profesi akuntan berlandaskan filsafat Jawa lebih bars, ruruh,wantah,duga prayoga,nastitidan tidak berfokus pada ardana. Karakter dhakah dalam dirinya perlahan sirna karena warok yang terbentuk telah mencapai Wiloka. Temuan ini memberikan aspek baru bagi pengembangan kurikulum program pendidikan akuntansi, agar lulusannya (akuntan) lebih dapat mengerti dan memaknai filosofi hidup manusia dari sudut pandang filsafat Jawa.Kata kunci: Etika; Perilaku; Karakter pendidikan profesi akuntan.